“I WAS SUPPORTED BY MY FAITH…”: VASYL’ KARKHUT’S FEAT IN LIFE AND CREATIVE WORK - Maftyn, N. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The article is dedicated to the analysis of wholeness of “life creating” and “text creating” of Vasyl’ Karkhut’s figure: a fighter for Ukraine’s independence, a talented writer on animals, doctor and phytotherapist. The article examines the factors influencing the formation of V. Karkhut’s worldview, his artistic abilities. In addition, it analyses the influence of Jack London’s and Dontsov’s aesthetic conception of “will neo-romanticism” on the formation of the psychological narrative of animal stories and novellas by the writer. It analyses the thematic, genre and style compass of the collection “Tsupke zhyttia”, an innovative search in the realm of architectonics of the genre of the novella.